Pengembangan Media Pembelajaran Berbasis Film Animasi terhadap Kemampuan Representasi Matematis Siswa - Winda, Winda; Haryadi, Rahman; Susiaty, Utin Desy (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the development of learning and student responses to animated film learning media on mathematical representation skills. The method used is development research with the ADDIE model (Analysis-Design-Development-Implement-Evaluate). This research was conducted at SMP Negeri 1 Mempawah Hulu with research subjects being 26 students in grade VIII. The instruments used were validation sheets, response questionnaires, and representative ability tests. Data analysis in this study was validity, effectiveness, and practicality. Based on the results of the study, the validity of the media and materials reached an average of 82.97% with very valid criteria, practicality reached an average of 81.80%, and effectiveness reached 76.92%. From the results of the study, it was concluded that animation-based learning media is feasible to be developed and has met the criteria for validity, practicality, and effectiveness.